Kegiatan Layanan Manasik Umroh dan Haji Mazq Tour and Travel - Alfina Nahwa Firdauzi; Maman Chatamallah (UNISBA Press, 2024)
Abstract. Umrah, as a spiritual and physical journey for Muslims, requires thorough preparation in terms of mental, physical, and material aspects to ensure a successful and accepted worship. The purpose of organizing the pilgrimage and Umrah, as regulated by Law No.13 of 2008, is to provide optimal guidance and protection through an efficient system and management of services. In this context, the guidance method for Umrah, particularly the Umrah rituals (manasik), is a crucial factor, and PT. MazQ Tour and Travel in Bandung introduces innovation by applying the Theatrical RBT method. This research aims primarily to (1) understand the implementation of Umrah ritual services at PT. MazQ Tour and Travel and (2) analyze the strengths and weaknesses in the application of the Umrah ritual guidance method in the company. Using a qualitative approach with a case study specification, data is collected through observation, interviews, and documentation. Data analysis follows the steps of case study analysis by Miles & Huberman, including data reduction, data presentation, and drawing conclusions. The results of this research are expected to provide insights for PT. MazQ Tour and Travel to enhance the effectiveness and efficiency of Umrah services. The implications of this study are also directed to assist stakeholders, including company management, employees, and prospective pilgrims, in better understanding the dynamics involved in organizing Umrah rituals. Abstrak. Ibadah umroh, sebagai perjalanan spiritual dan jasmani bagi umat Muslim, memerlukan persiapan yang matang dari segi mental, fisik, dan materi untuk memastikan kelancaran ibadah yang mabrur. Tujuan penyelenggaraan ibadah haji dan umroh, sebagaimana diatur dalam Undang-Undang No.13 Tahun 2008, adalah memberikan pembinaan dan perlindungan optimal melalui sistem dan manajemen pelayanan yang efisien. Dalam konteks ini, metode pembimbingan umroh, khususnya manasik umrah, menjadi faktor kunci, dan PT. MazQ Tour and Travel di Bandung memperkenalkan inovasi dengan menerapkan metode Teatrikal RBT. Penelitian ini bertujuan utama untuk (1) memahami pelaksanaan pelayanan manasik umroh di PT. MazQ Tour and Travel, serta (2) menganalisis kelebihan dan kekurangan dalam penerapan metode pembimbingan manasik umroh di perusahaan tersebut. Dengan menggunakan pendekatan kualitatif dan spesifikasi studi kasus, data diperoleh melalui observasi, wawancara, dan dokumentasi. Analisis data mengikuti langkah-langkah analisis studi kasus Miles & Huberman, mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini diharapkan dapat memberikan wawasan bagi PT. MazQ Tour and Travel dalam meningkatkan efektivitas dan efisiensi layanan umroh. Implikasi penelitian juga diarahkan untuk membantu pemangku kepentingan, termasuk manajemen perusahaan, karyawan, dan calon jamaah, agar lebih memahami dinamika yang terlibat dalam penyelenggaraan manasik umroh.